1992
DOI: 10.1111/j.1600-0447.1992.tb03241.x
|View full text |Cite
|
Sign up to set email alerts
|

5‐HT2 receptor antagonism and slow‐wave sleep in major depression

Abstract: Specific sleep disturbances such as reduced slow-wave sleep (SWS) and decreased serotonergic (5-HT) activity have been observed in depressive disorders. Ritanserin, a specific 5-HT2 receptor antagonist, has been shown to increase SWS in healthy subjects. This study explored the effects of a single dose or ritanserin (5 mg) on sleep electroencephalography in 18 major depressed patients and in 10 control subjects. Ritanserin affected SWS differently in the two groups. Although stage 3 increased significantly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Serotonin neuroendocrine studies in depressive illness have shown a blunted prolactin response to the 5-HT-releasing agent d-fenfluramine, which is mediated by the 5-HT 2A receptor (Cowen 1993). Differences in slow-wave sleep pattern response to the 5-HT 2A antagonist ritanserin between depressed patients and controls have also been reported (Staner et al 1992). Post mortem studies demonstrated increased 5-HT 2A receptors in the prefrontal cortex of suicide victims and depressed persons who died of natural causes (Arango et al 1990; Arora and Meltzer 1989b;Hrdina et al 1993;Stanley and Mann 1983), consistent with the hypothesis that 5-HT 2A receptors up-regulate in response to a defect in serotonergic neurotransmission.…”
Section: Serotonin In Late-life Depressionmentioning
confidence: 62%
See 1 more Smart Citation
“…Serotonin neuroendocrine studies in depressive illness have shown a blunted prolactin response to the 5-HT-releasing agent d-fenfluramine, which is mediated by the 5-HT 2A receptor (Cowen 1993). Differences in slow-wave sleep pattern response to the 5-HT 2A antagonist ritanserin between depressed patients and controls have also been reported (Staner et al 1992). Post mortem studies demonstrated increased 5-HT 2A receptors in the prefrontal cortex of suicide victims and depressed persons who died of natural causes (Arango et al 1990; Arora and Meltzer 1989b;Hrdina et al 1993;Stanley and Mann 1983), consistent with the hypothesis that 5-HT 2A receptors up-regulate in response to a defect in serotonergic neurotransmission.…”
Section: Serotonin In Late-life Depressionmentioning
confidence: 62%
“…Dysregulation of 5-HT function is believed to be involved in depression, impulsivity, and suicide (Arango et al 1992;Kennett 1991;Meltzer 1990;Staner et al 1992). Additionally, modulation of cholinergic neuronal activity by 5-HT may play a role in higher cognitive processes such as memory and 412 C.C.…”
Section: Anatomy Of the Serotonin Systemmentioning
confidence: 99%
“…The direct 5-HT 2C receptor blockade by a potent antagonist such as SB-206 553 has been shown to potentiate the antidepressant-like effects of imipramine in mice subjected to the forced swimming test (Yamada and Sugimoto, 2001). Although, up to date, a selective 5-HT 2C antagonist has not been demonstrated to be an effective antidepressant in large, double-blind, placebo-controlled clinical trials, there are clinical data to indicate that non-specific antagonists of 5-HT 2C receptors are effective in the treatment of depression (Strauss and Klieser, 1991;Staner et al, 1992) and alterations in 5-HT 2C receptor function and/or expression have been reported to occur in rats submitted to the learned helplessness test (Iwamoto et al, 2005) and in depressed patients who committed suicide, notably complex alterations in 5-HT 2C pre-mRNA editing sites preferences that suggests an overall decreased 5-HT 2C receptor activity in the prefrontal cortex of suicide victims with a history of major depression (Niswender et al, 2001;Gurevich et al, 2002;Iwamoto and Kato, 2003;Schmauss, 2003;Iwamoto et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…7 The mechanism of mirtazapine to improve sleep quality may depend on its selective 5-HT 2A/C antagonism more than on its H 1 antagonism. 8 It also found in other antidepressants such as ritanserin, nefazodone, and trazodone, which prolongs the duration of SWS. 8 It is an intriguing issue why only a higher dosage of mirtazapine (45 mg/d) induced sleepwalking in this depressed patient.…”
Section: Discussionmentioning
confidence: 99%